Social Network Strategy to Counter Acts of Terrorism in Indonesia: A Structural Hole Study - Agus Surya Bakti; Hafied Cangara; Dwia Aries Tina Palubuhu; Eriyanto Eriyanto (Ikatan Sarjana Komunikasi Indonesia, 2021)
The ISIS terrorist group still poses a serious threat in Indonesia, especially because it operates in a network (net-terrorism) so that the handling of this terrorist group often does not reach its roots. The research is aimed to reveal the social network strategy in resolving terrorist acts in Indonesia using a structural hole theory. The research method is a qualitative research approach with secondary data analysis from four sources: books, journal articles, previous related research, and the Law of the Republic of Indonesia. The data above is then processed with Ucinet-Draw to calculate the linkage score between members in the network and then see the movement map for each ISIS network in Indonesia: Jakarta, Poso, and Surabaya. Thus, this study proves that there is a gap in the structure of the ISIS group's communication network in Indonesia. The research results revealed that many terrorist acts in Indonesia had the same pattern, namely the strong communication network between terrorist actors. Terrorist actors carried out at least three tertius strategies, namely tertius gaudens, tertius inguens, and a combination of the two. Through the tertius strategy, the government will be able to play its most crucial role in taking preventive actions against actors in terrorist networks. Therefore, the government needed to carry out various integration strategies with various institutions to conduct deradicalization appropriately.